Management of Priapism: A Contemporary Review. (19th March 2019) - Mishra, Kirtishri; Loeb, Aram; Bukavina, Laura; Baumgarten, Adam; Beilan, Jonathan; Mendez, Melissa; DiGiorgio, Lorenzo; Fu, Liying; Carrion, Rafael
ABSTRACT: Introduction: Current management of ischemic priapism revolves around 3 principles: resolving the acute event, preserving erectile function, and reducing the risk of future recurrences. Although more conservative management options, such as aspiration, irrigation, and surgical shunts, are effective in many patients, those who are refractory to these interventions or have prolonged priapism may benefit from placement of a penile prosthesis (PP). Aim: To provide a comprehensive overview of priapism management, highlight the current literature on the utility of penile implants for refractory priapism, and provide insight from a high-volume center on surgical decision making and technique. Methods: A complete review of the current guidelines and associated literature was performed. Associated algorithms were evaluated, and our experience was overlaid on the data present in the literature. Main Outcome Measures: The current management algorithm for priapism was evaluated. Subsequently, the data on acute and delayed PP placement were assessed. Rates of postoperative infection, erectile dysfunction, and patient satisfaction were also examined. Results: Overall, both delayed and early PP implants are associated with higher rates of failure than routine PP implants. In patients with refractory or prolonged priapism, early implantation may be technically easier, with decreased loss of penile length and associated complications. Conclusion: Patients should be evaluated on an individual basis and counseled on the risks and benefits of PP implantation in early and delayed time frames. Although there is no definitive evidence at this time regarding the ideal device or timing of implantation, there are well-established pros and cons of malleable vs inflatable prostheses and of acute vs delayed implantation.